EXPLORING THE CORRELATION BETWEEN SEVERE PERSISTENT PSYCHOLOGICAL DISTRESS AND SURGICAL OUTCOMES IN WOMEN UNDERGOING MASTECTOMY FOR BREAST CANCER (Journal of Medical & Health Sciences Review, 2025)
Background: Depression and anxiety are prevalent in BC patients and may affect surgical factors. It is for this reason that it is important for health-care providers to understand the above correlation in view of enhancing quality patient care as well as the success of surgeries.Aim: The purpose of this work is to identify the correlation between the severity of persistent psychological distress and surgery outcomes in women with breast cancer, who have undergone mastectomy.Methods: An exploratory cross sectional descriptive study was undertaken with 300 women from a tertiary hospital who were to undergo mastectomy. The sample size was determined using the WHO sample sized estimate for prevalence studies. Self-reported psychological distress was measured by the Hospital Anxiety and Depression Scale (HADS) and surgical efficacy was judged by post operative complication, length of convalescence and patient satisfaction. Information obtained was analyzed using statistical software and results highlighted in colored tables, graphs and pie charts.Results: Persistent psychological distress had higher outcomes of being severely affected and these was strongly associated with adverse surgical outcomes. Postoperative distress was associated with higher complication rates (p